A newly isolated green alga Chlorella sp. KLSc59: potential for biohydrogen production - Sirawattanamongkol, Thanaporn; Maswanna, Thanaporn; Maneeruttanarungroj, Cherdsak (My University, 2020)
Hydrogen production from microalgae has attracted considerable attention due to its high energy content and as a renewable and environmentally friendly energy source. Various strains of microalgae have been reported to produce “biohydrogen”, but screening for new strains is still necessary to discover strains with higher hydrogen yields. A newly isolated hydrogen-producing green alga was screened and labeled Chlorella sp. KLSc59. The effect of extracellular pH, light intensity, external carbon sources, reducing agents, and nutrient deprivation on biohydrogen production of Chlorella sp. KLSc59 were investigated. Hydrogen yield was higher under anaerobic conditions. Under external pH 7.2 with 53.2 μmol photons m−2 s−1 light intensity and using acetate as a carbon source, the optimum hydrogen yield was 281 μmol H2 mg−1 Chl. Nutrient deprivation reduced the hydrogen yield. Several reducing agents were assessed, and 1 mM ethanol enhanced yield by 3 times for 850 μmol H2 mg−1 Chl, and 1 mM sodium dithionite increased yield by 2.7 times for 750 μmol H2 mg−1 Chl. Significantly, our new strain showed higher hydrogen yields ranging from 1.5 to 68 times compared with other microalgae. Thus, Chlorella sp. KLSc59 showed valuable potential for biohydrogen production.
Keywords: Biohydrogen; Chlorella sp. KLSc59; Chlorophyta; Yield optimization